Non‐pharmacological interventions to prevent hospital or nursing home admissions among community‐dwelling older people with dementia: A systematic review and meta‐analysis. (28th March 2020) - Lee, Den‐Ching A.; Tirlea, Loredana; Haines, Terry P.
Abstract: Older people with dementia more frequently experience episodes of hospital care, transferal to nursing home and adverse events when they are in these environments. This study synthesised the available evidence examining non‐pharmacological interventions to prevent hospital or nursing home admissions for community‐dwelling older people with dementia. Seven health science databases of all dates were searched up to 2 December 2019. Randomised controlled trials and comparative studies investigating non‐pharmacological interventions for older people with dementia who lived in the community were included. Meta‐analyses using a random‐effect model of randomised controlled trials were used to assess the effectiveness of interventions using measures taken as close to 12 months into follow‐up as reported. Outcomes were risk and rate of hospital and nursing home admissions. Risk ratio (RR) or rate ratios (RaR) with 95% confidence interval were used to pool results for hospital and nursing home admission outcomes. Sensitivity analyses were conducted to include pooling of results from non‐randomised trails. Twenty studies were included in the review. Community care coordination reduced rate of nursing home admissions [(2 studies, n  = 303 people with dementia and 86 patient–caregiver dyads), pooled RaR = 0.66, 95% CI (0.45, 0.97), I 2  = 0%, p  = .45]. Single interventions of psychoeducation and multifactorial interventions comprising of treatment and assessment clinics indicated no effect on hospital or nursing home admissions. The preliminary evidence of community care coordination on reducing the rate of nursing home admissions may be considered with caution when planning for community services or care for older people living with dementia.